Du wirst keine anderen Götter neben mir haben: theologische und (religions-)philosophische Implikationen der Mosaischen Unterscheidung Jan Assmanns - Rahner, Johanna (Zeitschrift für katholische Theologie, 2005)
Jan Assmann's theory of a necessary link between biblical monotheism and violence has been vociferously disclaimed. The present analysis critically examines Assmann's apocalyptic identification – arrived at in the wake of Jakob Taubes – of the World and God as the main feature of biblical monotheism. This critical evaluation of Assmann takes its departure from the centre of the bible's idea of God – i.e. the exodus and the 'Selbstvorstellungsformel'. At the same time the philosophical and theological potential of the 'Mosaische Unterscheidung' as a criteriology of religion is shown to be implicitly developed.